Fuzzy adaptive trajectory tracking control of work-class ROVs considering thruster dynamics. (1st January 2023) - Li, Mingjie; Yu, Caoyang; Zhang, Xiaochao; Liu, Chunhu; Lian, Lian
Abstract: Work-class remotely operated vehicles (ROVs) are widely used in oceanic observation and underwater operation, which are driven by hydraulic power. A fuzzy adaptive controller considering thruster dynamics is proposed to improve the trajectory tracking performance of work-class ROVs in this paper. The dynamics of the hydraulic motor driven thruster is much higher than the position and orientation tracking ability of work-class ROVs. Thus, the system is divided into two separate subsystems: out-loop position and orientation control system, and inner-loop hydraulic control system. A fuzzy adaptive algorithm is employed in the out-loop position and orientation controller, which estimates the system parameters and disturbances respectively. A disturbance observer is used in the inner-loop hydraulic controller to attenuate the uncertainties and disturbances. A second order filter is adopted to synthesize these two controllers, which generates a smooth hydraulic motor speed command with appropriate bandwidth and range. The stability of the whole control system is proved through Lyapunov theory. Simulation results demonstrate the effectiveness of the proposed trajectory tracking control strategy under parameter uncertainties and disturbances. Highlights: Fuzzy adaption is used to estimate system parameters and disturbances respectively. The dynamics of the hydraulic motor driven thruster is firstly taken into account. Out-loop and inner-loop control processes are synthesized with a second order filter.